Stem Cells as a Model of Study of SARS-CoV-2 and COVID-19: A Systematic Review of the Literature - CUEVAS-GONZALEZ, MARIA VERONICA (2021)
Background. The SARS-CoV-2 virus is the cause of the latest pandemic of the 21st century; it is responsible for the development of COVID-19. Within the multiple study models for both the biology and the treatment of SARS-CoV-2, the use of stem cells has been proposed because of their ability to increase the immune response and to repair tissue. Therefore, the objective of this review is to evaluate the role of stem cells against SARS-CoV-2 and COVID-19 in order to identify their potential as a study model and as a possible therapeutic source against tissue damage caused by this virus. Therefore, the following research question was established: What is the role of stem cells in the study of SARS-CoV-2 and the treatment of COVID-19? Materials and Methods. A search was carried out in the electronic databases of PUBMED, Scopus, and ScienceDirect. The following keywords were used: “SARS-CoV-2,” “COVID-19,” and “STEM CELL,” plus independent search strategies with the Boolean operators “OR” and “AND.” The identified reports were those whose main objective was the study of stem cells in relation to SARS-CoV-2 or COVID-19. For the development of this study, the following inclusion criteria were taken into account: studies whose main objective was the study of stem cells in relation to SARS-CoV-2 or COVID-19 and clinical case studies, case reports, clinical trials, pilot studies, in vitro, or in vivo studies